Clean production method for co-production of boric acid and calcium nitrate tetrahydrate by nitric acid method
Patent Information
- Application Number
- CN202611411870.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-20
AI Technical Summary
已公开的酸法工艺普遍采用硫酸作分解剂,副产石膏(CaSO4·2H2O),存在一些不足:石膏中残留硼酸,洗涤不充分时B2O3损失率达3%-5%,且堆积造成土壤和水体硼污染;副产物附加值低,市场容量有限,堆存占用土地;硫酸体系下硼酸与硫酸钙难以分离,洗涤水量大、废水含盐量高
(1)本申请采用硝酸法工艺,硝酸法分解硼钙石不产生硫酸钙沉淀,酸解过程中不会出现硫酸法常见的石膏包覆硼钙石表面的现象,因此高酸度下B2O3分解率可持续提高到99.0%以上,酸解液中B2O3含量稳定在75-85 g/L,同时,高酸度可以改变杂质的走向,使得MgO、Fe2O3、Al2O3以硝酸盐形式充分转入液相,SiO2以硅胶形式留在固相中,再经压滤随滤泥分离,不进入后续结晶工序,保证了硼酸产品的纯度;
Smart Images

Figure REF-OBJ-1789115996013-000001 
Figure REF-OBJ-1789115996013-000002 
Figure REF-OBJ-1789115996013-000003
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical production technology, and in particular to the production of boric acid, specifically a clean production process for boric acid using borate as raw material, nitric acid as a decomposing agent, and calcium nitrate tetrahydrate as a byproduct. Background Technology
[0002] Boric acid is a basic chemical raw material widely used in glass fiber, glazes, flame retardants, pharmaceuticals, electronics, and nuclear industries. my country's boron resources are mainly boromagnesia ore and sodium borate. Long-term large-scale mining has led to a gradual decline in high-grade boromagnesia ore reserves, while sodium borate mining suffers from high chloride content and low utilization rates of associated elements. Imports of colemanite (2CaO·3B₂O₃·5H₂O), abundant in Turkey and the United States, as a supplementary boron source, are increasing annually.
[0003] Industrially, the production of boric acid from boron-containing minerals mainly follows three routes: acid leaching, alkaline leaching, and ammonium bicarbonate leaching. Acid leaching, with its mild reaction conditions, low energy consumption, and small equipment investment, is the mainstream route for processing boron-calcium ore. Publicly available acid leaching processes generally use sulfuric acid as a decomposing agent, producing gypsum (CaSO4·2H2O) as a byproduct. However, this process has several drawbacks: residual boric acid remains in the gypsum; insufficient washing results in a 3%-5% loss of B2O3; and stockpiling causes boron pollution in soil and water. The byproduct has low added value, limited market capacity, and requires significant land use for storage. Furthermore, in sulfuric acid systems, boric acid and calcium sulfate are difficult to separate, resulting in large washing water volumes and high salinity in the wastewater.
[0004] Using nitric acid instead of sulfuric acid to decompose boron ore can avoid gypsum byproducts and obtain high-value-added calcium nitrate products. CN104229815A discloses a method for preparing boric acid and sodium nitrate by treating sodium borocalcite or boromagnesia ore with nitric acid. The boric acid mother liquor is recycled. When the calcium nitrate concentration reaches 250-400 g / L, sodium sulfate is added to convert calcium nitrate into sodium nitrate and calcium sulfate. After two-stage conversion, evaporation and concentration, and cooling crystallization, boric acid, sodium nitrate and basic magnesium carbonate are obtained respectively. This process also has some problems: it uses sodium borate or boromagnesia, but the process parameters for borocalcite are not disclosed; the mother liquor treatment process is lengthy, requiring the introduction of two conversion agents, sodium sulfate and sodium carbonate, resulting in a complex byproduct system; the final pH of the reaction is controlled in the range of 2.5-4.5, and there is a trade-off between the utilization rate of nitric acid and the decomposition rate of B2O3. When the pH is too high, the nitric acid is not excessive, but the decomposition rate is low; if the amount of nitric acid is increased to lower the pH, the residual free nitric acid will be lost with the mother liquor, resulting in waste. The existing technology does not provide a solution that takes both into account.
[0005] CN117682529A discloses a method for the comprehensive utilization of sodium borate ore resources, employing a two-step nitric acid hydrolysis process. The first step involves adding 75%-85% nitric acid and reacting at 80℃ for 48 minutes. After filtration, the remaining nitric acid is added for cooling and crystallization. This process has a short reaction time and clearly controlled endpoint, but it is designed specifically for sodium borate ore and does not provide a process scheme for borate ore.
[0006] When using borate as raw material, the ore has a high CaO content (23.0%-26.0%) and a low MgO content (1.5%-3.0%), which differs from the phase composition of sodium borate (approximately 7.5% Na₂O and 14% CaO). Borate does not contain Na, resulting in a relatively simple byproduct system. However, MgO and SiO₂ impurities, after entering the acid hydrolysis solution, remain as Mg(NO₃)₂ and silica gel, affecting the purity of boric acid crystallization and the stability of the mother liquor circulation. When using borate in conjunction with sodium borate, problems arise such as low B₂O₃ decomposition rate, accumulation of impurities in the mother liquor circulation, and poor purity of the byproduct calcium nitrate.
[0007] Furthermore, boric acid crystallization generally employs single-stage cooling crystallization or single-stage evaporation crystallization processes, which have drawbacks such as wide crystal particle size distribution, large amount of mother liquor entrainment, high centrifugal washing-to-water ratio, and high drying energy consumption. The boric acid drying process typically uses airflow drying or flash drying; a single drying method cannot simultaneously achieve rapid removal of surface water and deep removal of bound water, making it difficult for the moisture content of the dried product to consistently remain below 0.1%. Summary of the Invention
[0008] To address the shortcomings of existing technologies, this invention proposes a clean production process for boric acid using borate as raw material, nitric acid as a decomposing agent, and calcium nitrate tetrahydrate as a byproduct.
[0009] The technical problem to be solved by the present invention is achieved through the following technical solution: A clean production method for the co-production of boric acid and calcium nitrate tetrahydrate using nitric acid includes the following steps: S1 acid hydrolysis: Add process water from the water distribution tank to the reactor equipped with a stirrer and steam jacket, open the stirrer and steam valves, and raise the temperature to 60-75℃; [The text abruptly shifts to a seemingly unrelated topic:] ...particles meeting the D... 90 ≤75 μm borocalcite powder is added to the reactor at a solid-liquid mass-volume ratio of 1:(3.5-5) and stirred and moistened for 5-15 min. Nitric acid with a pre-measured mass concentration of 55%-60% is slowly added, and the temperature inside the reactor is controlled not to exceed 90℃ during the feeding process. After the feeding is completed, the temperature is raised to 90-98℃ and the reaction is maintained for 2-3 h. During the reaction, the endpoint is monitored by an online pH meter, and the pH at the endpoint is controlled at 0.8-1.5. S2 One-time plate and frame filter press: After the reaction is completed, the slurry is sent to the plate and frame filter press for solid-liquid separation by a transfer pump. The filter press pressure is controlled at 0.4-0.6 MPa and the filter press time is 15-25 min to obtain the primary acid hydrolysate and boric acid-containing filter mud. S3 filter mud re-dissolving and secondary filtration: The boric acid-containing filter mud obtained from S2 is sent to a mud tank, and process water from the water distribution tank is added at a mass-to-volume ratio of 1:(3-5). The mixture is stirred and re-dissolved at 60-75℃ for 15-30 min, and then sent to a plate and frame filter press for secondary filtration. The filtration pressure is controlled at 0.3-0.5 MPa and the filtration time is 10-20 min to obtain secondary acid hydrolysate and secondary filter mud. The secondary filter mud is re-dissolved and filtered again in the same way to obtain tertiary acid hydrolysate and tertiary filter mud. Both the secondary and tertiary acid hydrolysates are sent to the water distribution tank for later use, and the tertiary filter mud is sent to the stockyard. S4 Dual-Stage Cooling Crystallization: The acid hydrolysate obtained from S2 is temporarily stored in a storage tank and then pumped into a primary cooling crystallization tank. The cooling circulating water is turned on to cool the solution to 30-38℃, and the solution is kept at this temperature and stirred for 2-6 hours to carry out the first stage of crystallization. The refrigeration unit is then started to further cool the crystallization solution to -5~5℃, and the solution is kept at this temperature and stirred for 3-6 hours to carry out the second stage of crystallization. S5 Thickening and Centrifugation: The crystallized liquid obtained in S4 is sent to the thickener for thickening, and the supernatant is temporarily stored in the washing tank; the crystal slurry at the bottom of the thickener is sent to the centrifuge for solid-liquid separation, the centrifuged mother liquor is sent to the primary mother liquor buffer tank, and the boric acid wet crystals are sent to the drying process. S6 Combined Drying: The boric acid wet crystals obtained in S5 are fed into a fluidized bed dryer via a conveyor belt. The inlet air temperature is controlled at 130-155℃, the bed temperature at 95-115℃, and the material residence time at 8-15 min for the first stage of drying, reducing the free moisture content of boric acid to 1.5%-2.5%. Then, the crystals are fed into a disc dryer via an elevator. Circulating water is circulated in the disc dryer to cool the boric acid crystals, which have a high temperature after fluidized bed drying, to 25-35℃. The material residence time is 20-40 min, and the participating water vapor is further removed during the cooling process, reducing the total moisture content of boric acid to 0.05%-0.10%. The dried boric acid crystals are cooled, screened, and automatically packaged to obtain the finished boric acid product. S7 Primary Mother Liquor Treatment: The primary mother liquor obtained from S5 is sent to the evaporator balance tank and concentrated to a Baumé degree of 50-58°Bé under vacuum conditions of -0.09~-0.06 MPa and gauge pressure and temperature of 100-115℃ in a triple-effect evaporator. The concentrated liquid is then transferred to a concentration crystallization tank, and the crystallization temperature is controlled at 25-35℃ and the crystallization time is 5-8 h. The crystallized liquid is thickened and centrifuged to obtain calcium nitrate tetrahydrate and secondary mother liquor. The secondary mother liquor is returned to the water distribution tank for recycling. The centrifuged calcium nitrate tetrahydrate is packaged to obtain the finished calcium nitrate tetrahydrate product.
[0010] In this invention, the chemical composition of the borocalcite satisfies (mass percentage): B2O3 41.0%-43.0%, CaO2 3.0%-26.0%, SiO2 3.0%-7.0%, SO4 (calculated as SO3) ≤0.80%, Fe2O3 0.12%-0.30%, Al2O3 0.30%-0.80%, MgO 1.5%-3.0%, and moisture ≤1.0%; the particle size satisfies: the cumulative mass fraction of particles with a particle size not greater than 75 μm is not less than 82%.
[0011] In this invention, the amount of nitric acid added in S1 is 1.05-1.15 times the number of CaO moles in borate, ensuring that the reaction system has an excess of 5%-15% nitric acid.
[0012] In this invention, the heating stage described in S1 adopts a combination of steam jacket heating and internal coil heating. During the heating process, the steam flow rate is controlled by a rotor flow meter to keep the heating rate inside the reactor at 1.0-1.5 ℃ / min.
[0013] In this invention, both the primary and secondary cooling crystallizers in S4 are equipped with low-shear guide tube agitators, with the stirring linear speed controlled at 0.8-1.5 m / s to avoid crystal breakage and the generation of fine crystals.
[0014] In this invention, the temperature difference between the endpoint temperature of the first-stage cooling crystallization and the endpoint temperature of the second-stage cooling crystallization in S4 is controlled within the range of 30-40℃, and the ratio of the first-stage crystallization time to the second-stage crystallization time is controlled between 0.6 and 1.2.
[0015] In this invention, the centrifuge mentioned in S5 is a horizontal scraper centrifuge, and the centrifuge washing water is the diluted secondary acid hydrolysis solution obtained in S3, with the washing water temperature controlled at 40-60℃ and the washing water ratio at 0.08-0.15.
[0016] In this invention, the inlet temperature of the fluidized bed dryer described in S6 is controlled by PID, and the fluctuation range of the inlet temperature is controlled within ±3℃; the cooling temperature of the disc dryer is controlled by adjusting the circulating water flow rate, and the fluctuation range of the cooling temperature is controlled within ±2℃.
[0017] In this invention, the final secondary steam of the triple-effect evaporator described in S7 is condensed and then returned to the water distribution tank for use as process water for recycling, and the evaporation condensate reuse rate is not less than 85%.
[0018] In this invention, the process exhaust gas generated by this process is treated synergistically by a water film dust collector and an exhaust gas absorption tower. The absorbent is a 5%-10% nitric acid solution, and the concentration of nitrogen oxides in the exhaust gas after absorption is less than 30 mg / Nm³. 3 The exhaust gas absorbent is returned to the reactor for recycling.
[0019] In this invention, during the secondary mother liquor recycling process in S7, when Ca 2+ When the cumulative concentration reaches 350-450 g / L, part of the mother liquor undergoes evaporation concentration, cooling crystallization, and open-circuit treatment to control the Ca content in the mother liquor. 2+ The concentration remained stable between 300-400 g / L.
[0020] In this invention, the process water is a circulating feed liquid collected in a distribution tank. Its sources include the secondary acid hydrolysis solution obtained in S3, the secondary mother liquor obtained in S7, the condensate from the last effect secondary steam of the triple-effect evaporator in S7, and pure water or deionized water added during initial start-up or to replenish losses. After the circulation reaches a steady state, the process water contains, by mass percentage, 0.5%-5% free nitric acid, 0.2%-1.2% boric acid (calculated as B2O3), 3%-20% calcium nitrate, and 0.1%-1.0% magnesium nitrate, with the remainder being water. The free nitric acid and boric acid in the process water re-enter the acid hydrolysis process to participate in the reaction and crystallization, achieving the recovery and utilization of nitric acid and boric acid.
[0021] In this invention, the final pH of the reaction is controlled between 0.8 and 1.5. Below 0.8, the decomposition rate increases more slowly, but the burden of free nitric acid increases sharply. 0.8 is the critical point where the decomposition rate gains peak, but the cost of free acid has not yet spiraled out of control. Above 1.5, the decomposition rate declines rapidly. At this point, although the free acid content is very low, further increasing the pH would result in a pure loss of yield. 1.5 is the inflection point where the decomposition rate begins to decline significantly. Therefore, 0.8-1.5 is the optimal choice for the high-acidity acidolysis process of this invention, which aims to maintain acidity for decomposition while relying on mother liquor recycling to recover free acid and prevent it from spiraling out of control.
[0022] Compared with the prior art, the present invention has the following advantages: (1) This application adopts the nitric acid process. The nitric acid process does not produce calcium sulfate precipitation when decomposing borocalcite. During the acid hydrolysis process, the phenomenon of gypsum coating on the surface of borocalcite, which is common in the sulfuric acid process, will not occur. Therefore, the decomposition rate of B2O3 under high acidity can be continuously increased to more than 99.0%, and the B2O3 content in the acid hydrolysis solution is stable at 75-85 g / L. At the same time, high acidity can change the direction of impurities, so that MgO, Fe2O3, and Al2O3 are fully transferred into the liquid phase in the form of nitrates, while SiO2 remains in the solid phase in the form of silica gel. After pressure filtration, they are separated with the filter mud and do not enter the subsequent crystallization process, thus ensuring the purity of the boric acid product. (2) The reaction endpoint pH of the process in this application is controlled at 0.8-1.5, so that the acid hydrolysate contains a small amount of free nitric acid. The free nitric acid is retained in the primary mother liquor after entering the crystallization process with the acid hydrolysate. It is enriched in the secondary mother liquor during evaporation and crystallization, and is returned to the water distribution tank with the secondary mother liquor as acid hydrolysate feed liquid for recycling. The decomposition rate is guaranteed by the excess nitric acid, and the recycling of nitric acid material is realized. There is no loss of nitric acid, and the utilization rate of nitric acid is improved. (3) The acid hydrolysis process of this application adopts a segmented temperature control method of low temperature pre-wetting and high temperature reaction to suppress the rapid escape of nitric acid mist and nitrogen oxides in the initial stage of the reaction, effectively reducing the content of nitrogen oxides in the tail gas; the primary pressure filtration and filter mud resolution secondary pressure filtration process, and the secondary acid hydrolysis liquid is returned to the water distribution tank for recycling, effectively improving the boron recovery rate; the crystallization process adopts gradient dual-stage cooling crystallization, and the obtained boric acid crystals have a uniform particle size distribution; (4) This application uses direct evaporation crystallization to produce calcium nitrate tetrahydrate as a byproduct, without the need to introduce sodium sulfate or sodium carbonate for conversion. The byproduct system is simple and the calcium nitrate tetrahydrate has high purity. (5) This application adopts a combined fluidized bed and disc drying process. The fluidized bed quickly removes free water, while the disc drying deeply removes bound water, effectively reducing drying energy consumption. Attached Figure Description
[0023] Figure 1 This is a process flow diagram of the present invention; Figure 2 This is a curve showing the relationship between the decomposition rate of B2O3 and the final pH value in this invention. Figure 3 This is a comparison of the decomposition rate, recovery rate, and purity of Examples 1-3 of the present invention with Comparative Examples 1 and 2; Figure 4 This invention provides a comparison of the particle size distribution of boric acid obtained through single-stage and two-stage cooling crystallization. Figure 5 The XRD spectrum of calcium nitrate tetrahydrate obtained in Example 1 of this invention is shown.
[0024] In the diagram: 1. Water distribution tank; 2. Acid-resistant reactor; 3. Plate filter press I; 4. Acid hydrolysate storage tank; 5. Primary cooling crystallization tank; 6. Secondary freezing crystallization tank; 7. Thickener I; 8. Centrifuge I; 9. Fluidized bed dryer; 10. Disc dryer; 11. Slurry tank; 12. Plate filter press II; 13. Plate filter press III; 14. Primary mother liquor buffer tank; 15. Triple-effect evaporator; 16. Concentration crystallization tank; 17. Thickener II; 18. Centrifuge II; 19. Wash water tank. Detailed Implementation
[0025] The present invention will be further described below with reference to the accompanying drawings and specific preferred embodiments, but this does not limit the scope of protection of the present invention.
[0026] Unless otherwise specified, the raw materials, equipment, and testing standards used in the embodiments of this invention are all commercially available products, conventional industrial equipment, and national / industry general standards in the field.
[0027] Example 1
[0028] This embodiment provides a preferred clean production process for the co-production of boric acid and calcium nitrate tetrahydrate using the nitric acid method.
[0029] 1.1 Raw material preparation Chemical composition of raw boron-calcium stone (mass percentage): B2O3 42.30%, CaO 24.50%, SiO2 5.20%, SO4 (as SO3) 0.45%, Fe2O3 0.18%, Al2O3 0.55%, MgO 2.10%, moisture 0.85%; cumulative mass fraction of particles with a particle size not greater than 75 μm is 84.5%. After the circulation reaches steady state in this embodiment, the typical composition (mass percentage) of the process water in the water distribution tank is as follows: free nitric acid 3.2%, boric acid (calculated as B2O3) 0.6%, calcium nitrate 12.5%, magnesium nitrate 0.4%, and the remainder is water.
[0030] 1.2 Preparation process S1 Acidolysis: Add 2500 mL of process water from the water distribution tank to a 10 L acid-resistant glass reactor equipped with mechanical stirring, a constant temperature jacket, and an online pH meter. Start stirring at 90 r / min and start heating to 70℃. Add 1000 g of borocalcite powder to the reactor in four batches, stirring and wetting for 3-4 min after each batch, with a total feeding time of about 15 min. Slowly add 747 g of 58% nitric acid, controlling the reactor temperature to not exceed 88℃ during the addition process using the jacket cooling water. After the addition is complete, raise the temperature to 95℃ and maintain the reaction temperature for 2.5 h. Monitor the endpoint using the online pH meter during the reaction process; the endpoint pH is 1.05. S2 Single Plate and Frame Filtration: The reaction slurry is fed into a laboratory plate and frame filter press with a filtration area of 0.05 m². 2 The filtration pressure was controlled at 0.5 MPa and the filtration time at 20 min; approximately 3080 mL of primary acid hydrolysate was obtained, containing 78.5 g / L B2O3 and Ca. 2 + 56.2 g / L, Mg 2+ 4.8 g / L; 533 g of boric acid filter mud was obtained, with a moisture content of 42% and a B2O3 content of 2.8% (on a wet basis). S3 filter mud re-dissolving and secondary filtration: 533 g of boric acid-containing filter mud was added to 2130 mL of process water and stirred at 70℃ for 25 min to re-dissolve. It was then sent to a plate and frame filter press for secondary filtration, with the filtration pressure controlled at 0.4 MPa and the filtration time at 15 min. 2300 mL of secondary acid hydrolysate containing 8.6 g / L B2O3 and secondary filter mud were obtained. The secondary filter mud was re-dissolved and filtered again in the same manner to obtain tertiary acid hydrolysate and tertiary filter mud. Both the secondary and tertiary acid hydrolysates were sent to a water distribution tank for later use, while the tertiary filter mud was sent to the storage yard. S4 Dual-Stage Cooling Crystallization: 3080 mL of the primary acid hydrolysis solution is fed into a 5 L jacketed crystallizer. The cooling circulating water is turned on to lower the temperature to 35°C, and the solution is kept at this temperature and stirred for 5 h for the first stage of crystallization. Then, a low-temperature constant-temperature circulating bath is connected to further cool the crystallizer to 0°C, and the solution is kept at this temperature and stirred for 5 h for the second stage of crystallization. Both the primary and secondary crystallizers are equipped with low-shear guide tube stirrers with a stirring linear velocity of 1.0 m / s. S5 Thickening Centrifugation: The crystallized liquid obtained in S4 is allowed to stand for 40 min to thicken. The supernatant is temporarily stored in a washing tank, and the bottom crystal slurry is sent to a benchtop centrifuge for solid-liquid separation. The centrifuge washing water is a diluted secondary acid hydrolysis solution with a dilution ratio of 1:3, a washing water temperature of 50℃, and a washing water ratio of 0.10. After centrifugation, the moisture content of the boric acid wet crystals is 9.5%, and they enter the drying process. The centrifugation mother liquor is sent to a primary mother liquor buffer tank. S6 Combined Drying: Wet boric acid crystals are fed into a small fluidized bed dryer, with the inlet air temperature controlled at 145℃, the bed temperature at 108℃, and the material residence time at 12 min for the first stage of drying. After the first stage of drying, the moisture content of the boric acid is reduced to 2.0%. Then, the crystals are fed into a tray drying oven, where circulating water is introduced to cool the boric acid crystals, which are at a relatively high temperature after fluidized bed drying, to about 30℃. The material residence time is 30 min, during which residual moisture is further removed, and the total moisture content of the boric acid is reduced to 0.07%. After cooling, the boric acid is sieved to obtain 1142 g of finished boric acid product. S7 Primary Mother Liquor Processing: Approximately 2800 mL of primary mother liquor in the primary mother liquor buffer tank is concentrated to a Baumé degree of 54°Bé by vacuum evaporation in a rotary evaporator under conditions of vacuum degree -0.08 MPa and water bath temperature of 95℃. The concentrated liquid is then transferred to a crystallization tank, and the crystallization temperature is controlled at 30℃ for 7 hours. The crystallized liquid is thickened and centrifuged to obtain 1692 g of calcium nitrate tetrahydrate and 1530 mL of secondary mother liquor. The secondary mother liquor is returned to the water distribution tank for reuse. The centrifuged calcium nitrate tetrahydrate is packaged to obtain 1692 g of finished calcium nitrate tetrahydrate.
[0031] 1.3 Product Indicators B2O3 decomposition rate 99.2%, B2O3 recovery rate 97.8%, boric acid product (H3BO3) purity 99.92%, boric acid product moisture 0.07%, boric acid crystal D 60 / D10 Particle size ratio 2.4, calcium nitrate tetrahydrate [Ca(NO3)2·4H2O] purity 98.7%, nitric acid consumption per unit of boric acid (converted to 100% HNO3) 812 kg / t, fresh water consumption per unit of boric acid 1.05 m³ 3 / t.
[0032] Example 2
[0033] Based on Example 1, this embodiment uses different batches of raw materials to provide another clean production process for the co-production of boric acid and calcium nitrate tetrahydrate by nitric acid method.
[0034] 2.1 Raw material preparation Chemical composition of raw boron-calcium stone (mass percentage): B2O3 41.50%, CaO 25.20%, SiO2 4.10%, SO4 0.62%, Fe2O3 0.22%, Al2O3 0.68%, MgO 2.45%, moisture 0.92%; cumulative mass fraction of particles with a particle size not greater than 75 μm is 82.5%.
[0035] 2.2 Preparation process S1 acidolysis: Add 2410 mL of process water to a 10 L acid-resistant glass reactor and heat to 65℃; add 1000 g of borocalcite powder and stir to wet for 15 min; slowly add 785 g of 60% nitric acid, controlling the reactor temperature to not exceed 90℃ during the addition; after the addition is completed, heat to 96℃ and maintain the temperature for 2.8 h. The final pH of the reaction is 0.95. S2 First Plate and Frame Filtration: The reaction slurry was fed into a laboratory plate and frame filter press, and the filtration pressure was controlled at 0.45 MPa and the filtration time at 22 min; approximately 3090 mL of primary acid hydrolysate was obtained, containing 80.2 g / L of B2O3; 543 g of boric acid-containing filter mud was obtained. S3 filter mud re-dissolving and secondary filtration: Add the filter mud to 1900 mL of process water at a ratio of 1:3.5, stir and re-dissolve at 65℃ for 30 min, and then send it to a plate and frame filter press for secondary filtration, controlling the filtration pressure at 0.35 MPa and the filtration time at 18 min; obtain 2160 mL of secondary acid hydrolysate containing 7.9 g / L B2O3, and secondary filter mud; re-dissolve and filter the secondary filter mud again in the same way to obtain tertiary acid hydrolysate and tertiary filter mud; send the secondary and tertiary acid hydrolysates to the water distribution tank for later use, and send the tertiary filter mud to the storage yard; S4 Two-Stage Cooling Crystallization: The first acid hydrolysate is fed into a 5 L jacketed crystallizer and cooled to 33°C. The mixture is kept at this temperature and stirred for 4 hours to carry out the first stage of crystallization. Then, it is further cooled to -2°C and kept at this temperature and stirred for 4 hours to carry out the second stage of crystallization. The stirring speed is 1.2 m / s. S5 Thickening Centrifugation: After the crystallizing liquid is allowed to stand and thicken, the supernatant is temporarily stored in a washing tank, while the bottom crystal slurry is fed into a benchtop centrifuge for solid-liquid separation. The centrifuge washing water is a diluted secondary acid hydrolysis solution with a dilution ratio of 1:3, a washing water temperature of 45℃, and a washing water ratio of 0.12. After centrifugation, the moisture content of the boric acid wet crystals is 10.2%. S6 Combined Drying: Wet boric acid crystals are fed into a small fluidized bed dryer, with the inlet air temperature controlled at 140℃, the bed temperature at 105℃, and the material residence time at 10 min; a tray drying box is circulated with water to cool down to about 30℃, with the material residence time at 35 min. During the cooling process, residual moisture is further removed, and the final total moisture content of the boric acid is 0.08%. S7 Primary Mother Liquor Processing: The primary mother liquor is concentrated to a Baumé degree of 52°Bé by vacuum evaporation in a rotary evaporator under reduced pressure conditions of -0.075 MPa and 92°C water bath. The concentrate is then transferred to a crystallization tank, where the crystallization temperature is controlled at 28°C and the crystallization time is 6 hours. The crystallized liquid is thickened and centrifuged to obtain 1698 g of calcium nitrate tetrahydrate and 1540 mL of secondary mother liquor. After centrifugation, the calcium nitrate tetrahydrate is directly packaged to obtain the finished product, while the secondary mother liquor is returned to the water distribution tank.
[0036] 2.3 Product Indicators The decomposition rate of B2O3 is 98.8%, the recovery rate of B2O3 is 97.5%, the purity of boric acid product (H3BO3) is 99.90%, the purity of calcium nitrate tetrahydrate [Ca(NO3)2·4H2O] is 98.5%, and the nitric acid consumption per unit of boric acid (converted to 100% HNO3) is 825 kg / t.
[0037] Example 3
[0038] Based on Example 1, this embodiment uses different batches of raw materials to provide another clean production process for the co-production of boric acid and calcium nitrate tetrahydrate by nitric acid method.
[0039] 3.1 Raw material preparation Chemical composition of raw boron-calcium stone (mass percentage): B2O3 42.80%, CaO 23.50%, SiO2 6.50%, SO4 0.55%, Fe2O3 0.15%, Al2O3 0.42%, MgO 1.80%, moisture 0.78%; cumulative mass fraction of particles with a particle size not greater than 75 μm is 86.0%.
[0040] 3.2 Preparation process S1 acidolysis: Add 2500 mL of process water to a 10 L acid-resistant glass reactor and heat to 75℃; add 1000 g of borocalcite powder and stir to wet for 12 min; slowly add 729 g of 56% nitric acid, controlling the reactor temperature to not exceed 87℃ during the addition; after the addition is completed, heat to 94℃ and maintain the temperature for 2.3 h. The final pH of the reaction is 1.20. S2 First Plate and Frame Filtration: The reaction slurry was fed into a laboratory plate and frame filter press, and the filtration pressure was controlled at 0.55 MPa and the filtration time was 18 min; approximately 3100 mL of primary acid hydrolysate was obtained, containing 76.8 g / L of B2O3; 492 g of boric acid-containing filter mud was obtained. S3 filter mud re-dissolving and secondary filtration: Add the filter mud to 2210 mL of process water at a ratio of 1:4.5, stir and re-dissolve at 72℃ for 20 min, and then send it to a plate and frame filter press for secondary filtration, controlling the filtration pressure at 0.45 MPa and the filtration time at 14 min; obtain 2290 mL of secondary acid hydrolysate containing 6.5 g / L B2O3, and secondary filter mud; re-dissolve and filter the secondary filter mud again in the same way to obtain tertiary acid hydrolysate and tertiary filter mud; send the secondary and tertiary acid hydrolysates to the water distribution tank for later use, and send the tertiary filter mud to the storage yard; S4 Two-Stage Cooling Crystallization: The first acid hydrolysate is fed into a 5 L jacketed crystallizer and cooled to 36°C. The mixture is then kept at this temperature and stirred for 5.5 h for the first stage of crystallization. The mixture is then further cooled to 2°C and kept at this temperature and stirred for 5.5 h for the second stage of crystallization. The stirring speed is 0.9 m / s. S5 Thickening Centrifugation: After the crystallizing liquid is allowed to stand and thicken, the supernatant is temporarily stored in a washing tank, while the bottom crystal slurry is fed into a benchtop centrifuge for solid-liquid separation. The centrifuge washing water is a diluted secondary acid hydrolysis solution with a dilution ratio of 1:3, a washing water temperature of 55℃, and a washing water ratio of 0.09. After centrifugation, the moisture content of the boric acid wet crystals is 9.0%. S6 Combined Drying: The wet boric acid crystals are fed into a small fluidized bed dryer, with the inlet air temperature controlled at 150℃, the bed temperature at 112℃, and the material residence time at 14 min for the first stage of drying. Then, they are sent to a tray drying box, where the circulating water cools the crystals to about 30℃ and the material residence time is 28 min. The final total moisture content of the boric acid is 0.06%. S7 Primary Mother Liquor Processing: The primary mother liquor is concentrated to a Baume degree of 56°Bé by vacuum evaporation in a rotary evaporator under reduced pressure conditions of -0.085 MPa and 98°C water bath. The concentrate is then transferred to a crystallization tank, where the crystallization temperature is controlled at 32°C and the crystallization time is 7.5 hours. The crystallized liquid is thickened and centrifuged to obtain 1694 g of calcium nitrate tetrahydrate and 1500 mL of secondary mother liquor. After centrifugation, the calcium nitrate tetrahydrate is packaged to obtain the finished product, and the secondary mother liquor is returned to the water distribution tank.
[0041] 3.3 Product Indicators The decomposition rate of B2O3 is 99.4%, the recovery rate of B2O3 is 98.0%, the purity of boric acid product (H3BO3) is 99.94%, the purity of calcium nitrate tetrahydrate [Ca(NO3)2·4H2O] is 98.9%, and the nitric acid consumption per unit of boric acid (converted to 100% HNO3) is 805 kg / t.
[0042] Example 4
[0043] This embodiment is an industrial-scale pilot production of the process of the present invention, implemented according to the process steps of Embodiment 1. Each process uses commercially available or existing industrial equipment, and the scale of a single reactor is scaled up as follows: The acidolysis process uses a 30,000 L acid-resistant reactor with stirring, steam jacket and internal coil, lined with glass or Hastelloy alloy, and a water tank with a volume of 50,000 L. 5,000 kg of borocalcite powder and 15,000 L of process water are added to a single reactor, followed by the slow addition of 4,480 kg of 58% nitric acid. The reactor temperature is controlled not to exceed 88℃ during the feeding process, and the temperature is raised to 95℃ and maintained for 2.5 h. The final pH is controlled at 0.8-1.5.
[0044] The filtration process uses 80 m 2 The diaphragm plate and frame filter press has a filtration pressure of 0.5 MPa and a filtration time of 20 min. The boric acid-containing filter mud is sent to the mud tank and re-dissolved with process water at a mass-to-volume ratio of 1:4. After secondary filtration, the secondary acid hydrolysate is returned to the water distribution tank. The secondary filter mud is re-dissolved and filtered again in the same way. The tertiary acid hydrolysate is returned to the water distribution tank, and the tertiary filter mud is sent to the storage yard.
[0045] The crystallization process uses a 40,000 L primary cooling crystallizer and a 40,000 L secondary freezing crystallizer, both equipped with low-shear guide tube stirrers with a stirring linear velocity of 0.8-1.5 m / s. The first stage cools to 30-38℃ and holds for 2-6 hours, and the second stage cools to -5~5℃ and holds for 3-6 hours.
[0046] The centrifugation process uses a φ6000 mm thickener and a horizontal scraper centrifuge. The wash water is a diluted secondary acid hydrolysate with a temperature of 40-60℃ and a wash-to-water ratio of 0.08-0.15.
[0047] The drying process uses a fluidized bed dryer (inlet air temperature 130-155℃, bed temperature 95-115℃, residence time 8-15 min) and a disc dryer (circulated water is introduced to cool down to 25-35℃, residence time 20-40 min) in series.
[0048] The evaporation and crystallization process uses a triple-effect evaporator (vacuum degree -0.09~ -0.06 MPa, gauge pressure and temperature 100-115℃) to concentrate the primary mother liquor to a Baume degree of 50-58°Bé. The concentrate is then crystallized in a concentration and crystallization tank at 25-35℃ for 5-8 hours. After thickening and centrifugation, calcium nitrate tetrahydrate is obtained.
[0049] During scale-up, the reaction temperature, endpoint pH, nitric acid concentration, solid-liquid ratio, Baumé degree, vacuum degree, crystallization temperature and time, drying temperature and residence time, and other quantitative parameters remained consistent with those of the pilot-scale example. The reactor volume, feed rate, plate and frame filter area, crystallizer volume, and heat exchange area were scaled up proportionally to the production capacity. The stirring linear velocity was selected according to the principle of maintaining geometric similarity. The production line, with an annual output of 70,000 tons of boric acid and approximately 100,000 tons of calcium nitrate tetrahydrate as a byproduct, processes approximately 61,000 tons of borocalcite annually and consumes approximately 57,000 tons of nitric acid (equivalent to 100% HNO3) annually. The single-reactor operation cycle is consistent with Example 1, with a B2O3 decomposition rate of no less than 99.0% and a recovery rate of no less than 97.5%. The product quality indicators are comparable to those of the pilot-scale example.
[0050] Example 5
[0051] This embodiment includes a comparative experiment, which compares the present invention with several comparative examples to determine the technical effectiveness of the present invention.
[0052] 5.1 Case Setup Comparative Example 1 Using the same raw materials as in Example 1, and operating according to the process conditions of the prior art: (1) Mix 1000 g of borocalcite (containing 42.30% B2O3 and 24.50% CaO) with 5000 mL of water, heat to 60℃, add 510 g of 68% nitric acid, heat to 90℃, keep the temperature for 60 min, and control the pH at the end of the reaction to 3.5. (2) The slurry is filtered by a filter press to obtain acid hydrolysate and a small amount of boron mud. The acid hydrolysate is sent to a cooling crystallizer and cooled to 25°C to precipitate boric acid crystals. (3) After centrifugation to separate boric acid, the mother liquor is returned to the acid hydrolysis process for recycling. When the concentration of calcium nitrate in the mother liquor reaches 250-400 g / L, sodium sulfate is added according to the theoretical amount for conversion, and then sodium carbonate is added for conversion. (4) The converted solution is evaporated and concentrated to 40°Bé Baumé, cooled and crystallized to precipitate a mixed slurry of boric acid and sodium nitrate, which is then separated by gravity to obtain boric acid and sodium nitrate.
[0053] The products obtained in Comparative Example 1 were: B2O3 decomposition rate 97.5%, B2O3 recovery rate 94.8%, boric acid product (H3BO3) purity 99.62%, nitric acid consumption per unit of boric acid (converted to 100% HNO3) 852 kg / t, and byproducts were calcium sulfate, basic magnesium carbonate, and calcium nitrate, with no calcium nitrate tetrahydrate.
[0054] Compared with Example 1, Comparative Example 1 shows that the B2O3 recovery rate of the present invention is 3.0% higher, the unit nitric acid consumption is reduced by 47 kg / t, and the tetrahydrate calcium nitrate, which meets the standards for compound agricultural fertilizer, is directly produced as a byproduct without the need to introduce sodium sulfate and sodium carbonate as conversion agents.
[0055] Comparative Example 2 Using the same raw materials as in Example 1, and operating according to the process conditions of the prior art: (1) Add 1000 g of borate to 3000 g of water, add 80% of the total amount of nitric acid required, that is, about 440 g of 50% nitric acid, and react at 80℃ for 48 min to obtain the first slurry; after filtration, add the remaining 20% nitric acid to the filtrate, cool to 20℃ to crystallize; filter to obtain boric acid crystals and the second filtrate, wash and dry the boric acid crystals to obtain the boric acid product; (2) The second filtrate reacts with the decalcifying agent sulfuric acid to obtain the third filtrate, which is then concentrated and crystallized to obtain sodium nitrate product.
[0056] The products obtained in Comparative Example 2 showed the following: B2O3 decomposition rate 98.2%, B2O3 recovery rate 96.0%, boric acid product (H3BO3) purity 99.80%, and boric acid crystal D. 60 / D 10 With a particle size ratio of 3.6, the nitric acid consumption per unit of boric acid (converted to 100% HNO3) is 835 kg / t.
[0057] Compared with Example 1, Comparative Example 2 shows that the B2O3 recovery rate of the present invention is 1.8% higher, the boric acid crystal particle size distribution is more uniform, and the byproduct is calcium nitrate tetrahydrate instead of sodium nitrate-calcium sulfate mixed system, and the byproduct treatment process is simpler.
[0058] Comparative Example 3 Using the same raw materials and some steps as in Example 1, step S4 is replaced with a single-stage cooling crystallization process. Specifically, the primary acid hydrolysate is directly fed into a cooling crystallization tank, cooled to 0°C, kept warm and stirred for 10 h, and then thickened and centrifuged.
[0059] Product obtained in Comparative Example 3: Boric acid crystals D 60 / D 10 Particle size ratio 3.8, centrifugation entrainment mother liquor volume 35% (wet basis), wash water consumption per unit of boric acid 0.18 m 3 / t.
[0060] Compared with Example 1, Comparative Example 3 shows that the two-stage cooling crystallization process of the present invention results in a more uniform boric acid crystal particle size distribution and a 35% reduction in the amount of mother liquor carried over during centrifugation.
[0061] Comparative Example 4 Using the same raw materials and some steps as in Example 1, step S6 is replaced with a single airflow drying process, specifically: the wet boric acid crystals are fed into an airflow dryer, the inlet temperature is controlled at 165°C, the outlet temperature at 95°C, and the material residence time is 25 min.
[0062] The product obtained in Comparative Example 4 had a moisture content of 0.18% and a drying energy consumption of 0.42 GJ / t per unit of boric acid.
[0063] Compared with Example 1, the fluidized bed-disc combined drying process of the present invention reduced the moisture content of boric acid product to 0.07% and reduced drying energy consumption by 22%.
[0064] Comparative Example 5 Using the same raw materials and some steps as in Example 1, step S7 was replaced with a sodium sulfate conversion route. Specifically, sodium sulfate was added to the mother liquor in stoichiometric proportions, and the mixture was stirred at 80°C for 45 min to generate calcium sulfate precipitate. The precipitate was then filtered, washed, and separated. Sodium carbonate was added to the filtrate in stoichiometric excess of 5%, and the mixture was stirred at 70°C for 60 min to generate basic magnesium carbonate precipitate. The precipitate was then filtered, washed, and separated. The converted solution was evaporated and concentrated to a Baume degree of 40°Bé, and cooled to 25°C to crystallize a mixed slurry of boric acid and sodium nitrate. The boric acid and sodium nitrate were then separated by gravity.
[0065] The product obtained in Comparative Example 5: Sodium sulfate consumption per unit of boric acid is approximately 830 kg / t, sodium carbonate consumption per unit of boric acid is approximately 50 kg / t, two conversion processes are involved (sodium sulfate conversion and sodium carbonate conversion), byproducts are calcium sulfate, basic magnesium carbonate, and sodium nitrate, and SO4 is introduced into the mother liquor. 2- Na + It accumulates with each cycle.
[0066] Compared with Example 1, Comparative Example 5 shows that the direct crystallization route of the present invention eliminates the need for sodium sulfate and sodium carbonate conversion reagents, eliminates two conversion steps and the associated heating, filtration, and washing processes, and does not introduce SO4 into the mother liquor. 2- and Na + The only byproduct is calcium nitrate tetrahydrate.
[0067] 5.2 Product and Technology Comparison Table 1 shows the comparison of the main technical and economic indicators of Examples 1-3 and Comparative Examples 1-5 of the present invention.
[0068] 5.3 Results Analysis The results above show that the B2O3 decomposition rate in Examples 1-3 was 98.9%-99.4%, the B2O3 recovery rate was 97.5%-98.0%, and the boric acid product purity (H3BO3) was 99.90%-99.94%. The three indicators fluctuated little among the examples, indicating that the process has good repeatability within the parameter range specified in the scheme. The decomposition rate increases with the increase of the raw material B2O3 content, while the unit nitric acid consumption (equivalent to 100% HNO3) decreases with the increase of the decomposition rate. The two trends are consistent and conform to the stoichiometric law of borate acid hydrolysis.
[0069] Compared with Comparative Example 1, Example 1 showed a 1.7% higher B2O3 decomposition rate, a 3.0% higher recovery rate, a 0.30% higher boric acid purity, and a 40 kg / t lower unit nitric acid consumption. This indicates that under high acidity conditions (pH 0.8-1.5 at the reaction endpoint), combined with secondary pressure filtration and mother liquor recycling, the decomposition rate, recovery rate, and nitric acid utilization rate of B2O3 can be simultaneously improved. Compared with Comparative Example 2, Example 1 showed a 1.0% higher B2O3 decomposition rate, a 1.8% higher recovery rate, and a lower boric acid crystal D. 60 / D 10 The particle size ratio decreased from 3.6 to 2.4, indicating that single-stage high-acidity acid hydrolysis combined with two-stage cooling crystallization is superior to two-step acid hydrolysis combined with single-stage crystallization in terms of decomposition rate and crystal particle size uniformity.
[0070] Comparative Example 3 only replaced single-stage cooling crystallization with two-stage cooling crystallization; the remaining processes were the same as in Example 1. Its boric acid crystals D 60 / D 10 The particle size ratio was 3.8, higher than 2.4 in Example 1, indicating that the two-stage cooling crystallization is the key process for obtaining uniform boric acid crystals. Comparative Example 4 only replaced the fluidized bed-disc combined drying with a single airflow drying, while the rest of the process was the same as in Example 1. The moisture content of its boric acid product increased from 0.07% to 0.18%, and the unit drying energy consumption increased from 0.33 GJ / t to 0.42 GJ / t, indicating that the series connection of fluidized bed and disc drying took into account both rapid removal of free water and deep removal of bound water, and reduced drying energy consumption. Comparative Example 5 replaced the by-product process with a sodium sulfate conversion route, while the rest of the process was the same as in Example 1. Its decomposition rate, recovery rate, purity, and moisture content were consistent with Example 1, but it required an additional consumption of about 830 kg / t of sodium sulfate and about 50 kg / t of sodium carbonate. The by-product changed from a single calcium nitrate tetrahydrate to a mixture of calcium sulfate, basic magnesium carbonate, and sodium nitrate, indicating that the direct evaporation crystallization route eliminated the input of conversion reagents and simplified the by-product system.
Claims
1. A clean production method for the co-production of boric acid and calcium nitrate tetrahydrate using nitric acid, characterized in that, Includes the following steps: S1 acid hydrolysis: Add process water from the water distribution tank to the reactor equipped with a stirrer and steam jacket, open the stirrer and steam valves, and raise the temperature to 60-75℃; [The text abruptly shifts to a seemingly unrelated topic:] ...particles meeting the D... 90 ≤75 μm borocalcite powder is added to the reactor at a solid-liquid mass-volume ratio of 1:(3.5-5) and stirred and moistened for 5-15 min. Nitric acid with a pre-measured mass concentration of 55%-60% is slowly added, and the temperature inside the reactor is controlled not to exceed 90℃ during the feeding process. After the feeding is completed, the temperature is raised to 90-98℃ and the reaction is maintained for 2-3 h. During the reaction, the endpoint is monitored by an online pH meter, and the pH at the endpoint is controlled at 0.8-1.
5. S2 One-time plate and frame filter press: After the reaction is completed, the slurry is sent to the plate and frame filter press for solid-liquid separation by a transfer pump. The filter press pressure is controlled at 0.4-0.6 MPa and the filter press time is 15-25 min to obtain the primary acid hydrolysate and boric acid-containing filter mud. S3 filter mud re-dissolving and secondary filtration: The boric acid-containing filter mud obtained from S2 is sent to a mud tank, and process water from the water distribution tank is added at a mass-to-volume ratio of 1:(3-5). The mixture is stirred and re-dissolved at 60-75℃ for 15-30 min, and then sent to a plate and frame filter press for secondary filtration. The filtration pressure is controlled at 0.3-0.5 MPa and the filtration time is 10-20 min to obtain secondary acid hydrolysate and secondary filter mud. The secondary filter mud is re-dissolved and filtered again in the same way to obtain tertiary acid hydrolysate and tertiary filter mud. Both the secondary and tertiary acid hydrolysates are sent to the water distribution tank for later use, and the tertiary filter mud is sent to the stockyard. S4 Dual-Stage Cooling Crystallization: The acid hydrolysate obtained from S2 is temporarily stored in a storage tank and then pumped into a primary cooling crystallization tank. The cooling circulating water is turned on to cool the solution to 30-38℃, and the solution is kept at this temperature and stirred for 2-6 hours to carry out the first stage of crystallization. The refrigeration unit is then started to further cool the crystallization solution to -5~5℃, and the solution is kept at this temperature and stirred for 3-6 hours to carry out the second stage of crystallization. S5 Thickening and Centrifugation: The crystallized liquid obtained in S4 is sent to the thickener for thickening, and the supernatant is temporarily stored in the washing tank; the crystal slurry at the bottom of the thickener is sent to the centrifuge for solid-liquid separation, the centrifuged mother liquor is sent to the primary mother liquor buffer tank, and the boric acid wet crystals are sent to the drying process. S6 Combined Drying: The boric acid wet crystals obtained from S5 are conveyed into a fluidized bed dryer via a conveyor belt. The inlet air temperature is controlled at 130-155℃, the bed temperature at 95-115℃, and the material residence time at 8-15 min for the first stage of drying, reducing the free moisture content of boric acid to 1.5%-2.5%. Then, the crystals are conveyed into a disc dryer via an elevator. Circulating water is circulated in the disc dryer to cool the boric acid crystals, which have a high temperature after fluidized bed drying, to 25-35℃. The material residence time is 20-40 min, and the participating water vapor is further removed during the cooling process, reducing the total moisture content of boric acid to 0.05%-0.10%. The cooled boric acid crystals are then screened and automatically packaged to obtain the finished boric acid product. S7 Primary Mother Liquor Treatment: The primary mother liquor obtained from S5 is sent to the evaporator balance tank and concentrated to a Baumé degree of 50-58°Bé under vacuum conditions of -0.09~-0.06 MPa and gauge pressure and temperature of 100-115℃ in a triple-effect evaporator. The concentrated liquid is then transferred to a concentration crystallization tank, and the crystallization temperature is controlled at 25-35℃ and the crystallization time is 5-8 h. The crystallized liquid is thickened and centrifuged to obtain calcium nitrate tetrahydrate and secondary mother liquor. The secondary mother liquor is returned to the water distribution tank for recycling. The centrifuged calcium nitrate tetrahydrate is packaged to obtain the finished calcium nitrate tetrahydrate product.
2. The method according to claim 1, characterized in that, The chemical composition of the borocalcite, by mass percentage, meets the following requirements: B2O3 41.0%-43.0%, CaO 23.0%-26.0%, SiO2 3.0%-7.0%, SO4 (calculated as SO3) ≤0.80%, Fe2O3 0.12%-0.30%, Al2O3 0.30%-0.80%, MgO 1.5%-3.0%, and moisture ≤1.0%; the particle size meets the following requirement: the cumulative mass fraction of particles with a particle size not greater than 75 μm is not less than 82%.
3. The method according to claim 1, characterized in that, The amount of nitric acid added in S1 is 1.05-1.15 times the number of moles of CaO in borate, ensuring that the reaction system has an excess of 5%-15% nitric acid.
4. The method according to claim 1, characterized in that, In the S4 primary and secondary cooling crystallizers, the stirring linear speed is controlled at 0.8-1.5 m / s, the temperature difference between the endpoint temperature of primary cooling crystallization and the endpoint temperature of secondary cooling crystallization is controlled within the range of 30-40℃, and the ratio of primary crystallization time to secondary crystallization time is controlled between 0.6-1.
2.
5. The method according to claim 1, characterized in that: In S6, the inlet temperature of the fluidized bed dryer is controlled by PID, and the fluctuation range of the inlet temperature is controlled within ±3℃. The cooling temperature of the disc dryer is controlled by adjusting the circulating water flow rate, and the fluctuation range of the cooling temperature is controlled within ±2℃.
6. The method according to claim 1, characterized in that, In S5, the centrifuge washing water uses the diluted secondary acid hydrolysis solution obtained in S3, and the washing water temperature is controlled at 40-60℃ and the washing water ratio is 0.08-0.
15. In S7, the last effect secondary steam of the triple-effect evaporator is condensed and sent back to the water distribution tank for use as process water circulation, and the evaporation condensate recycling rate is not less than 85%.
7. The method according to claim 1, characterized in that, The process exhaust gas generated during the process is treated by a combination of water film dust removal and exhaust gas absorption tower. The absorbent is a 5%-10% nitric acid solution. After absorption, the concentration of nitrogen oxides in the exhaust gas is less than 30 mg / Nm³. 3 The exhaust gas absorbent is returned to the reactor for recycling.
8. The method according to claim 1, characterized in that, In S7, during the secondary mother liquor recycling process, when Ca... 2+ When the cumulative concentration reaches 350-450 g / L, part of the mother liquor undergoes evaporation concentration, cooling crystallization, and open-circuit treatment to control the Ca content in the mother liquor. 2+ The concentration remained stable between 300-400 g / L.
9. The method according to claim 1, characterized in that, The process water is a circulating feed liquid collected in a distribution tank. Its sources include the secondary acid hydrolysis liquid obtained in S3, the secondary mother liquor obtained in S7, the condensate of the secondary steam from the last effect of the triple-effect evaporator in S7, and pure water or deionized water added during the initial start-up or to replenish losses. After the circulation reaches a steady state, the process water contains, by mass percentage, 0.5%-5% free nitric acid, 0.2%-1.2% boric acid (calculated as B2O3), 3%-20% calcium nitrate, and 0.1%-1.0% magnesium nitrate, with the remainder being water.
Citation Information
Patent Citations
Method for preparing boric acid and sodium nitrate by treating ulexite (kramerite) or ascharite with nitric acid
CN104229815A
Method for comprehensively utilizing ulexite ore resources
CN117682529A